TRYING TO GET CULTURE! - van der Riet , Mary (PINS-Psychology in Society, 2025)
Ross, R (2004) Culture and cognition: Implications for theory and method. Thousand Oaks, Ca: Sage. Norbert Ross proposes a “new ethnography and an enhanced cognitive science” (p172) in response to his concern with the connection between culture and cognition. Ross’s focus is partly on methodology, but it is also on the subject matter of both psychology and anthropology. Ross uses his position of familiarity with these two disciplines to argue that anthropologists should return to a study of human thinking and behaviour with respect to culture; whilst on the other hand, psychology does not sufficiently understand, or account for, the impact of culture.